2011
DOI: 10.1167/iovs.10-6659
|View full text |Cite
|
Sign up to set email alerts
|

Integrity of the Cone Photoreceptor Mosaic in Oligocone Trichromacy

Abstract: Findings are consistent with the visual deficits being caused by a reduced number of healthy cones in the two brothers and the adult female. In the unrelated adult subject, no structural basis for the disorder was found. These data suggest two distinct groups on the basis of structural imaging. It is proposed that the former group with evidence of a reduction in cone numbers is more in keeping with typical OT, with the latter group representing an OT-like phenotype. These two groups may be difficult to readily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 27 publications
8
24
1
Order By: Relevance
“…Our measured cone density values are similar to anatomic and scanning laser ophthalmoscope measurements from previous studies, 37,44,[47][48][49][50][56][57][58] however the differences in image acquisition, cone identification, and sampling make direct comparisons difficult. Peak cone density measurements were intended to mimic manually selected windows of highest quality, so we anticipated the measurements from this sampling method would most closely resemble histological data.…”
Section: Measuring Cone Density and The Effect Of Samplingsupporting
confidence: 84%
“…Our measured cone density values are similar to anatomic and scanning laser ophthalmoscope measurements from previous studies, 37,44,[47][48][49][50][56][57][58] however the differences in image acquisition, cone identification, and sampling make direct comparisons difficult. Peak cone density measurements were intended to mimic manually selected windows of highest quality, so we anticipated the measurements from this sampling method would most closely resemble histological data.…”
Section: Measuring Cone Density and The Effect Of Samplingsupporting
confidence: 84%
“…The extent of macular cone mosaic disruption was more severe compared with cone dysfunction syndromes like achromatopsia and oligocone trichromacy. [22][23][24] In cases with minimal or no nystagmus, permitting better imaging closer to fovea, the degree of perifoveal cone photoreceptor disruption was consistent with the extent of photoreceptor IS-OS junction disruption noted on SD-OCT. Previous studies have consistently reported reasonable correlation between IS-OS junction disruption and absence of visible cones at the fovea and perifovea in cone dysfunction syndromes 23,24 and a wide range of retinal conditions.…”
Section: Discussionmentioning
confidence: 54%
“…[22][23][24] In cases with minimal or no nystagmus, permitting better imaging closer to fovea, the degree of perifoveal cone photoreceptor disruption was consistent with the extent of photoreceptor IS-OS junction disruption noted on SD-OCT. Previous studies have consistently reported reasonable correlation between IS-OS junction disruption and absence of visible cones at the fovea and perifovea in cone dysfunction syndromes 23,24 and a wide range of retinal conditions. 27,50,51 Further, the cone mosaic and density were also markedly abnormal in regions outside the fovea where SD-OCT showed less marked IS-OS disruption; the presence of intact rod photoreceptors in the region is the likely reason for this relative IS-OS preservation.…”
Section: Discussionmentioning
confidence: 54%
“…70 This has recently been demonstrated in human patients using flood-illuminated adaptive optics imaging, 71,72 although this needs to be examined with higher resolution devices to confirm how universal this feature is across a larger patient population and whether rods are also involved. 10,[12][13][14][15][16]18,[39][40][41][42][43][44][45][46][47][48][49][50]52,[56][57][58]62,63,71,72,98,99 A B…”
Section: Albinismmentioning
confidence: 99%